Selexipag Treatment for Pulmonary Arterial Hypertension : A Literature Review - Hamidah, Niswah; Yuliati, Amik (Faculty of Medical - UPN Veteran Jawa Timur, 2024)
Background. To review the current evidence regarding the use of selexipag in the treatment of PAH, evaluating its effectiveness and safety. Methods. Literature searching was conducted by collecting data through databases such as PubMed, Google Scholar, and ScienceDirect using search terms included